Vulnerable in the end – Longitudinal study among medical students on mental health and personal and work-related resources over a 5.5-year-period - Schneider, Kurt; Breuer, G.; Luibl, Lena; Paulsen, F.; Scholz, Michael; Burger, P. H.M. (Annals of Anatomy-Anatomischer Anzeiger, 2023)
Background: Mental health problems are common in medical professionals and their development already starts at the undergraduate level. Studies on medical students can replicate higher prevalence for depression and burnout in this group, but they normally compare semester cohorts in an anonymized, cross-sectional approach and without a preventive perspective. Methods: We surveyed medical students at the beginning and end of their medical curriculum and collected data on burnout, depressivity, work related experience and salutogenesis parameters with validated self-administered questionnaires. Most remarkably we obtained the data from the same 58 individuals after 5.5 years, representing data of the highest quality in order to compare the mental health status at the beginning and the end of our students´ medical curriculum. Results: Our results not only show a severe exacerbation of physical, mental and emotional burnout in the participants at the end of their studies. The students also do not seem to have sufficient personal (resilience) or social resources (e.g. experience of social support) for coping with their mental health problems around the time of their graduation. Conclusions: Our participants reflect a development of mental health during their medical studies at university that is paving the way to the devastating prevalence of mental disorders and suicide in health professionals. From our results we derive an urgent need to integrate self-care and active coping in the learning goals of medical curricula.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Burnout; Healthcare Professional; Mental Health; Resilience